Long term mortality after lower extremity amputation in South Africa - Husein, Salah (Department of Surgery, 2020)
Introduction: Long-term mortality after lower extremity amputation is not well reported in low- and middleincome countries. The primary aim of this study was to report 30-day and one-year mortality after lower extremity amputation in South Africa. The secondary objective was to report risk factors for one-year mortality. Methods: This was a retrospective cohort study of patients undergoing lower extremity amputations at New Somerset Hospital from October 1, 2015, to October 31, 2016. A medical record review was undertaken to identify co-morbidities, operation details, and perioperative mortality rate. Outcome status was defined as alive, dead, or lost to follow-up. Outcomes at 30 days and one year were reported. Results: There were 152 patients; 90 (59%) males and the median age (interquartile range, IQR) was 60 (54-67) years. At 30 days, 102 patients were traced and 12 (12%) were dead. At one year, 86 (57%) were traced and 37 (43%) were dead. Conclusion: At this South African hospital, 43% of patients undergoing lower extremity amputations were dead after one year. In resource-constrained settings, mortality data are necessary when considering resource allocation for lower extremity amputations and essential surgical care packages.